THE DEVELOPMENT OF HIGH-CAPACITY MACHINE-TOOL FOR PRODUCTION OF THE STEEL FIBER AND GRIT - N. V. Shirokij; V. F. Hramtsov (Литьë и металлургия)
The developments of high-capacity machine-tool for production of steel fiber and grid are given.